POLITICAL MUDDLE OF AMERICAN GOVERNMENT IN DANCE NATION (2018) BY CLARE BARRON - Suci Rahmadhani; Muhd. Al-Hafizh (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue of the political muddle of American government and to find out how the contribution of fictional elements (character, setting, plot/conflict, and stage direction) in revealing the issue of the political muddle of American government. This analysis is done through text-based and context-based interpretation which is related to the concept of Power Relation by Michel Foucault. The results of this analysis shows the kinds of the political muddle of American government on the outside and on the inside of America.